Building Democracy from Below: Lessons from Western Uganda - King, Sophie; Hickey, Sam (The Journal of Development Studies, 2016)
How to achieve democratisation in the neo-patrimonial and agrarian env ironments that predominate in sub-Saharan Africa continues to present a challenge for both development theory and practice. Drawing on inten sive fieldwork in Western Uganda, this paper argues that Charles Tilly ’s ‘democratisation as process’ provides us with the framework require d to explain the ways in which particular kinds of association can adv ance democratisation from below. Moving beyond the current focus on ho w elite-bargaining and certain associational forms may contribute to l iberal forms of democracy, this approach helps identify the intermedia te mechanisms involved in building democracy from below, including the significance of challenging categorical inequalities, notably through the role of producer groups, and of building trust networks, cross-cl ass alliances and synergistic relations between civil and political so ciety. The evidence and mode of analysis deployed here help suggest al ternative routes for supporting local efforts to build democracy from below in sub-Saharan Africa.
Keywords: FRUGAL